Solidariedade intergeracional familiar após a recoabitação. - Cunha, Ubiracelma Carneiro da (2022)
There has been an increase in multigenerational households due to re-cohabitation. Many older adults are heads of households and welcome back their children, grandchildren and even great-grandchildren. In this way, changes occur in the relational dynamics of family members, influencing the aspects that permeate intergenerational family solidarity. This thesis aimed to understand the intergenerational family solidarity in multigenerational homes after cohabitation. Specifically, the aim was: to characterise the feelings and evaluations expressed by the generations regarding their relationships; identify the proximity, frequency, and characteristics of interactions between generations; identify conflict factors and strategies used to deal with them; to analyse the perception of generations about the support provided and received between them; point out the expectations of filial and parental obligations related to family roles. This qualitative research in which three multigenerational families participated resulted from a re-cohabitation by their children and grandchildren. One member of each generation was interviewed, totalling nine participants. They answered a sociodemographic questionnaire and a semi-structured interview, as well as, during the interview, other instruments were carried out: List of feelings, Social Support Escort Model, and the Perception of Family Support Inventory (IPSF). The information obtained through these instruments was analysed using the thematic content analysis technique. The results showed that: (1) The generations expressed positive, negative, and ambivalent feelings throughout the experiences shared in the time of multigenerational family life; (2) All participants included family members with whom they live in multigenerational homes in their social support network. However, there were differences in the perception of proximity and exchanges of social support; (3) Co-residence was found to make intergenerational relationships more prone to tension and conflict; (4) In the relationships between generations, the presence of conflicts and situations that involved solidarity coexisted, confirming the statement that there is no relationship of exclusion between solidarity and conflict; (5) The first and second generations pointed to “family care” as a central aspect in the support scenario they share; (6) The presence of norms related to family loyalties were evidenced, which feed the expectations of filial and parental obligations under the exercise of care roles in these family arrangements; (7) All interviewees identified the presence of one or more family members who feel overloaded with the practice of some roles. Thus, the results show the need to cultivate bonds of affection that support the solution of conflicts and moments of transition and crisis in this type of family arrangement. It is considered that this thesis contributed to guide practices and interventions in the health area, especially in Clinical Psychology and Psychogerontology, aimed at families and generations.